A solid-state electrolyte composite and a preparation method thereof, a solid-state electrolyte membrane, a battery, a battery pack, and an electrical device
Patent Information
- Application Number
- CN202510500257.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2026-10-23
AI Technical Summary
然而现有固态电解质普遍存在着稳定性差(尤其是对水分不稳定)等问题,即使在露点控制环境中短时间暴露也容易发生性能恶化,其离子电导率降低,电池的循环寿命等性能变差
[0025]本发明的实施,至少具有如下有益效果:通过在固态电解质复合物中引入锂化沸石,并控制锂化沸石与固态电解质的质量比为1:(4~70),能够提高固态电解质复合物的稳定性,尤其可提高其对水分的稳定性,减少固态电解质复合物的水含量,抑制固态电解质复合物在含有水汽的环境(如空气)中暴露后的水含量的增加、以及由此导致的固态电解质复合物的离子电导率等性能恶化问题,提高固态电解质复合物在含有水汽的环境中暴露后的离子电导率保持率,改善电池的循环寿命等性能。
Smart Images

Figure BDA0005368950270000161 
Figure BDA0005368950270000181 
Figure BDA0005368950270000182
Abstract
Description
Technical Field
[0001] This invention relates to the field of batteries, specifically to a solid electrolyte composite and its preparation method, a solid electrolyte membrane, a battery, a battery pack, and electrical equipment. Background Technology
[0002] Lithium-ion batteries, as an important energy storage method, are gradually developing towards higher energy density and higher safety. Liquid batteries, which use electrolytes, face challenges in terms of safety due to the inherent safety risks of leakage and flammability of the organic electrolyte. In contrast, solid-state batteries, employing solid-state electrolytes, offer intrinsic safety and high energy density, and are gaining increasing attention and application.
[0003] In solid-state batteries, commonly used solid electrolytes include sulfide solid electrolytes and / or halide solid electrolytes. These solid electrolytes have high ionic conductivity, making them the preferred choice for developing solid-state batteries. However, existing solid electrolytes generally suffer from poor stability (especially instability to moisture). Even short-term exposure in a dew-point controlled environment can easily lead to performance degradation, resulting in decreased ionic conductivity and reduced battery cycle life and other performance characteristics. Summary of the Invention
[0004] This invention provides a solid electrolyte composite and its preparation method, a solid electrolyte membrane, a battery, a battery pack, and an electrical device, which can improve the stability of the solid electrolyte composite, especially its stability against moisture, suppress the decrease in its ionic conductivity, and improve the cycle life and other performance of the battery, effectively overcoming the defects of the prior art.
[0005] In one aspect, the present invention provides a solid electrolyte composite comprising a lithiated zeolite and a solid electrolyte, wherein the mass ratio of the lithiated zeolite to the solid electrolyte is 1:(4-70).
[0006] According to one embodiment of the present invention, the mass ratio of the lithium zeolite to the solid electrolyte is 1:(4-50).
[0007] According to one embodiment of the present invention, the lithium content in the lithiated zeolite is 1.5% to 25% by mass.
[0008] According to one embodiment of the present invention, the lithium content in the lithiated zeolite is 1.8% to 6.5% by mass.
[0009] According to one embodiment of the present invention, the solid electrolyte includes a sulfide solid electrolyte and / or a halide solid electrolyte.
[0010] According to one embodiment of the present invention, the sulfide solid electrolyte comprises Li 6-aPS 5-a X 1+a One or more of LGPS, LPS, and Li2S-P2S5 glass-ceramic solid electrolytes, wherein the Li 6-a PS 5-a X 1+a X in the equation is a halogen, 0 ≤ a ≤ 0.8; and / or, the halide solid electrolyte includes Li b MX c O d The Li b MX c O d In this context, X represents a halogen, M represents a transition metal element, 1≤b≤3, 1≤c≤6, and 0≤d≤1.
[0011] In another aspect, the present invention provides a method for preparing the above-mentioned solid electrolyte complex, comprising the following steps: ball milling a mixture containing the lithium zeolite and the solid electrolyte to obtain the solid electrolyte complex.
[0012] According to one embodiment of the present invention, the preparation process of the lithiated zeolite includes: performing at least one lithiation treatment on the zeolite molecular sieve to obtain the lithiated zeolite; the lithiation treatment process includes: soaking the zeolite molecular sieve in a solution containing a first lithium source for at least 0.5 h.
[0013] According to one embodiment of the present invention, the first lithium source includes lithium halide and / or lithium hydroxide; and / or, the lithium ion concentration of the solution containing the first lithium source is greater than or equal to 0.5 mol / L; and / or, the preparation process of the lithiated zeolite includes: subjecting the zeolite molecular sieve to multiple lithiation treatments to obtain lithiated zeolite; wherein, for each adjacent two lithiation treatments, the lithium ion concentration of the solution containing the first lithium source used in the previous lithiation treatment is less than the lithium ion concentration of the solution containing the first lithium source used in the subsequent lithiation treatment.
[0014] According to one embodiment of the present invention, the preparation process of the zeolite molecular sieve includes: mixing an inorganic alkali, a first aluminum source, and water to obtain a first solution; mixing the first solution, the alkali solution, and the first silicon source at a temperature ≤10°C, stirring at a temperature less than or equal to 10°C for at least 10 minutes, and then stirring at room temperature for at least 1 hour; subsequently carrying out a first hydrothermal reaction at 90–110°C, separating the solid and liquid, and drying the obtained solid product to obtain the zeolite molecular sieve.
[0015] According to one embodiment of the present invention, the inorganic alkali includes sodium hydroxide and / or potassium hydroxide; and / or, the first aluminum source includes aluminum hydroxide; and / or, the first silicon source includes silicate; and / or, the alkali in the alkaline solution includes sodium hydroxide and / or potassium hydroxide; and / or, the time of the first hydrothermal reaction is 2 to 10 hours.
[0016] According to one embodiment of the present invention, the preparation process of the lithiated zeolite includes: mixing a second silicon source, a second lithium source, and water, and stirring at 40°C to 80°C for 0.5h to 2h to obtain a first mixture; mixing a second aluminum source, a third lithium source, and water, and stirring at 40°C to 80°C for 0.5h to 2h to obtain a second mixture; mixing the first mixture and the second mixture, and then carrying out a second hydrothermal reaction at 150°C to 200°C to obtain a hydrothermal reaction product; and sintering the hydrothermal reaction product to obtain the lithiated zeolite.
[0017] According to one embodiment of the present invention, the second silicon source comprises silicon dioxide; and / or, the second lithium source comprises lithium hydroxide; and / or, the second aluminum source comprises aluminum oxide; and / or, the third lithium source comprises lithium hydroxide; and / or, the sintering temperature is 450°C to 800°C.
[0018] In another aspect, the present invention provides a solid electrolyte membrane comprising the above-described solid electrolyte composite and / or a solid electrolyte composite prepared according to the above-described method for preparing the solid electrolyte composite.
[0019] According to one embodiment of the present invention, the mass percentage of the solid electrolyte complex in the solid electrolyte membrane is 90% to 100%.
[0020] According to one embodiment of the present invention, a third binder is further included, wherein the mass percentage of the third binder in the solid electrolyte membrane is 0 to 10%.
[0021] In another aspect, the present invention provides a battery comprising the above-described solid electrolyte membrane.
[0022] According to one embodiment of the present invention, the battery is a solid-state battery.
[0023] In another aspect, the present invention provides a battery pack including the battery described above.
[0024] In another aspect, the present invention provides an electrical device comprising the aforementioned battery or battery pack.
[0025] The implementation of this invention has at least the following beneficial effects: by introducing lithiated zeolite into the solid electrolyte complex and controlling the mass ratio of lithiated zeolite to solid electrolyte to be 1:(4-70), the stability of the solid electrolyte complex can be improved, especially its stability to moisture, reducing the water content of the solid electrolyte complex, suppressing the increase in water content after exposure to a water-containing environment (such as air), and the resulting performance degradation problems such as the ionic conductivity of the solid electrolyte complex, improving the retention rate of ionic conductivity of the solid electrolyte complex after exposure to a water-containing environment, and improving the cycle life and other performance of the battery. Detailed Implementation
[0026] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below. The specific embodiments listed below are merely descriptions of the principles and features of the present invention, and the examples are only for explaining the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0027] This invention provides a solid electrolyte composite comprising lithiated zeolite and a solid electrolyte, wherein the mass ratio of lithiated zeolite to solid electrolyte is 1:(4-70).
[0028] According to the inventors' research, in the above-mentioned solid electrolyte composite system, lithiated zeolite has high hydrophilicity and is more likely to absorb water than the solid electrolyte. As a water-absorbing material, lithiated zeolite is combined with the solid electrolyte to form a solid electrolyte composite. Water can be preferentially locked in the lattice of lithiated zeolite, thereby avoiding the corrosion of the solid electrolyte by water and the resulting degradation of the solid electrolyte's ionic conductivity and other properties. At the same time, lithiated zeolite contains lithium, which, as a lithium-ion conductor, can provide lithium-ion transport channels, further avoiding problems such as the decay of lithium-ion conductivity in the solid electrolyte composite.
[0029] According to the inventors' research, in the above-mentioned solid electrolyte composite system, if the mass ratio of lithiol zeolite to solid electrolyte is too small (<1:70), the amount of lithiol zeolite relative to solid electrolyte is too small, resulting in high water content, low ionic conductivity, and poor battery capacity and cycle life. Conversely, if the mass ratio of lithiol zeolite to solid electrolyte is too large (>1:4), the amount of lithiol zeolite relative to solid electrolyte is too large, which will reduce the ionic conductivity of the solid electrolyte composite and also affect the battery's cycle life. At the same time, as the mass ratio of lithiol zeolite to solid electrolyte increases, the retention rate of ionic conductivity of the solid electrolyte composite after exposure to a water-containing environment (such as air) generally shows a trend of first increasing and then decreasing. Therefore, by controlling the mass ratio of lithium zeolite to solid electrolyte within the range of 1:(4-70), the water content of the solid electrolyte complex can be reduced while simultaneously improving the ionic conductivity and other properties of the solid electrolyte complex. This also improves the stability of the solid electrolyte complex, especially its stability against moisture, suppressing the increase in water content after exposure to moisture-containing environments (such as air) and the resulting deterioration in properties such as ionic conductivity. Furthermore, it enhances the retention rate of ionic conductivity of the solid electrolyte complex after exposure to moisture-containing environments, thereby improving the cycle life and other performance characteristics of the battery.
[0030] Furthermore, compared to combining a solid electrolyte with unlithiated zeolite (containing no lithium), this embodiment of the invention combines a solid electrolyte with lithiated zeolite. The lithiated zeolite can further act as an ion conductor, providing a lithium ion transport channel, thereby reducing the impact on the ionic conductivity of the solid electrolyte and further ensuring the ionic conductivity and other properties of the solid electrolyte composite.
[0031] Therefore, based on the excellent ionic conductivity and stability of the solid electrolyte composite, even when exposed to a water-containing environment, the solid electrolyte composite can suppress the increase of water content and the deterioration of ionic conductivity, thereby ensuring the battery's capacity and improving its rate performance and cycle life.
[0032] For example, in the above-mentioned solid electrolyte complex, the mass ratio of lithium zeolite to solid electrolyte can be 1:4, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, 1:22, 1:24, 1:26, 1:28, 1:30, 1:32, 1:34, 1:36, 1:38, 1:40, 1:42, 1:44, 1:46, 1:48, 1:50, 1:55, 1:60, 1:65, 1:70, or any combination thereof.
[0033] In some embodiments, the mass ratio of lithium zeolite to solid electrolyte in the above-mentioned solid electrolyte complex is 1:(4-50), which is beneficial to further reduce the water content of the solid electrolyte complex, improve its ionic conductivity, and enhance the battery's capacity and cycle life.
[0034] In this embodiment of the invention, the mass m0 of the solid electrolyte complex can be measured; then, the solid electrolyte complex can be soaked in water to separate the lithiated zeolite (particulate product) from it, and the mass m1 of the lithiated zeolite is measured. Then, the mass of the solid electrolyte in the solid electrolyte complex is basically equal to the difference between m0 and m1 (i.e., m0-m1). Then, the mass ratio of lithiated zeolite to solid electrolyte (m1:(m0-m1)) is calculated.
[0035] To reduce the reaction between the solid electrolyte and water in the solid electrolyte complex, the solid electrolyte complex can be soaked in alkaline water with a pH of 11 to 14, specifically alkaline water with a pH of 12.
[0036] In addition, after soaking the solid electrolyte complex in water, the resulting particulate product is dried at a temperature of 80-120℃, but in practice, drying at 120℃ is preferred. After drying, the mass m1 of the particulate product is measured.
[0037] Specifically, lithiated zeolites contain lithium, which exists in the form of lithium compounds. Specifically, lithiated zeolites include zeolite molecular sieves and lithium-containing materials present in the zeolite molecular sieves, including lithium compounds.
[0038] Specifically, zeolite molecular sieves are zeolites that can be used as molecular sieves, and conventional zeolite molecular sieves in the art can be used in the embodiments of the present invention.
[0039] In some embodiments, lithium-containing materials may include lithium aluminosilicate, which is beneficial for improving the stability and ionic conductivity of solid electrolytes.
[0040] In some embodiments, the mass percentage of lithium in the lithiated zeolite can be 1.5% to 25%, for example, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 3%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, or any combination thereof.
[0041] Further research by the inventors revealed that introducing lithium into zeolite can improve its properties, such as ionic conductivity. However, the number of lithium insertion sites in lithiated zeolite is limited. By further controlling the lithium content in lithiated zeolite, it is beneficial for lithium to be more fully inserted into the zeolite lattice. Lithium inserted into the zeolite lattice further improves the ionic conductivity and other properties of lithiated zeolite. Therefore, by further controlling the mass percentage of lithium in lithiated zeolite within the range of 1.5% to 25%, it is beneficial to improve the stability and ionic conductivity of the solid electrolyte. In particular, when the mass percentage of lithium in lithiated zeolite is 1.8% to 6.5%, it is beneficial to further improve the ionic conductivity and other properties of the solid electrolyte composite, while also improving the rate performance and cycle life of the battery.
[0042] In this embodiment of the invention, after obtaining the solid electrolyte membrane (e.g., by disassembling the battery and removing the solid electrolyte membrane from the battery), the solid electrolyte membrane can be soaked in water to separate the lithiated zeolite (particulate product), and then the lithium content in the lithiated zeolite can be tested by inductively coupled plasma spectrometry (ICP).
[0043] To reduce the reaction between the solid electrolyte and water in the solid electrolyte membrane sample, the solid electrolyte membrane can be soaked in alkaline water with a pH of 11 to 14, specifically alkaline water with a pH of 12.
[0044] In addition, after immersing the solid electrolyte membrane sample in water, the resulting particulate product is dried at a temperature of 80-120℃, but 120℃ is preferred in practice. After drying, the solid particulate product is then subjected to ICP and other tests.
[0045] Generally, the particle size of lithium zeolite can be 0.5 to 10 μm, for example, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any combination thereof.
[0046] In this embodiment of the invention, the solid electrolyte may include sulfide solid electrolyte and / or halide solid electrolyte. By combining the sulfide solid electrolyte and / or halide solid electrolyte with lithiated zeolite to form a solid electrolyte complex, water is preferentially locked in the lattice of lithiated zeolite, thereby suppressing the water absorption corrosion of the sulfide solid electrolyte and / or halide solid electrolyte, as well as the resulting performance degradation of the solid electrolyte such as ionic conductivity.
[0047] Specifically, sulfide solid electrolytes may include sulfide electrolytes of the Argyrodites type, specifically including Li 6-a PS 5-a X1+a .
[0048] In some embodiments, the sulfide solid electrolyte includes Li 6-a PS 5-a X 1+a One or more of LGPS, LPS, and Li2S-P2S5 glass-ceramic solid electrolytes, Li 6-a PS 5-a X 1+a X in the halogen can be Cl, Br or I, 0≤a≤0.8, where a is, for example, a range of 0, 0.2, 0.4, 0.5, 0.6, 0.8 or any two of them.
[0049] Specifically, Li 6-a PS 5-a X 1+a It may include Li6PS5Cl and / or Li 5.5 PS5Cl 1.5 LGPS may include Li 10 GeP2S 12 LPS may include Li7P3S 11 .
[0050] Furthermore, the chemical formula of the Li2S-P2S5 glass-ceramic solid electrolyte can be represented as (Li2S). x (P2S5) y x and y represent the molar ratio of Li2S and P2S5 in the Li2S-P2S5 glass-ceramic solid electrolyte, and x:y is, for example, a range of 1:3, 1:2, 1:1, 2:1, 3:1 or any two of them.
[0051] In some embodiments, the halide solid electrolyte includes Li b MX c O d The Li b MX c O d In this context, X represents a halogen, M represents a transition metal element, 1≤b≤3, 1≤c≤6, and 0≤d≤1. Specifically, M may include one or more of Y, In, Zr, and Nb, where b can be 1, 2, or 3, c can be 1, 2, 3, 4, 5, or 6, and d can be 0 or 1.
[0052] For example, Li b MX c O d This may include electrolyte products formed by oxygen doping of Li3YCl6, Li3InCl6, LiZrCl5, LiNbCl, or any of the aforementioned electrolytes (i.e., Li...). b MX cO d One or more of the following (d>0), but not limited to:
[0053] In some specific embodiments, Li b MX c O d This may include Li3YCl6, Li3InCl6, LiZrCl5, LiNbCl, Li 1.75 ZrCl 4.75 O 0.5 One or more of them.
[0054] In some embodiments, the solid electrolyte may include Li6PS5Cl, Li 10 GeP2S 12 Li 1.75 ZrCl 4.75 O 0.5 Li 5.5 PS5Cl 1.5 One or more of these components can be used to adapt to lithium zeolite, thereby improving the stability and ionic conductivity of solid electrolytes.
[0055] The present invention also provides a method for preparing the above-mentioned solid electrolyte complex, comprising the following steps: ball milling a mixture containing lithium zeolite and solid electrolyte to obtain the solid electrolyte complex.
[0056] As mentioned above, the mass ratio of lithium zeolite to solid electrolyte is 1:(4-70). By controlling the mass ratio of the two within this range, a solid electrolyte composite can be prepared through the above preparation process, which can improve the stability and ionic conductivity of the solid electrolyte composite and improve the cycle life of the battery.
[0057] In this embodiment of the invention, a mixture containing lithiated zeolite and solid electrolyte can be ball-milled by dry ball milling and / or wet ball milling to obtain a solid electrolyte composite.
[0058] In this embodiment of the invention, the ball milling process can be carried out in an inert atmosphere, which includes, for example, nitrogen and / or argon, but is not limited thereto.
[0059] In practice, lithium zeolite and solid electrolyte can be mixed, and the resulting mixture can be ball-milled under an inert atmosphere for a time ranging from 4 to 10 hours, such as 4, 5, 6, 7, 8, 9, or 10 hours, or any combination thereof. After ball milling, the powder is collected to obtain the solid electrolyte composite.
[0060] In this embodiment of the invention, lithiated zeolite can be prepared by a two-step method, that is, firstly, zeolite molecular sieve is prepared, and then the zeolite molecular sieve is lithiated by impregnation or other methods; or, lithiated zeolite can also be prepared by a one-step method, that is, a lithium source is introduced during the preparation of zeolite molecular sieve to prepare lithiated zeolite.
[0061] In one embodiment, the lithiated zeolite is prepared by a two-step method (lithiation treatment of zeolite molecular sieve by impregnation). The preparation process of the lithiated zeolite may include: performing at least one lithiation treatment on the zeolite molecular sieve to obtain the lithiated zeolite; wherein each lithiation treatment (lithium-ion exchange treatment) includes: immersing the zeolite molecular sieve in a solution containing a first lithium source for at least 0.5 h, for example, immersion for 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h or any combination thereof.
[0062] When performing a lithiation process, after soaking, solid-liquid separation is carried out, the obtained solid product is washed with water, and then dried to obtain lithiated zeolite.
[0063] When multiple lithiation processes are performed, solid-liquid separation is carried out after each lithiation process, and the resulting solid product (soaked zeolite molecular sieve) is used for the next lithiation process. After the last lithiation process, solid-liquid separation is performed, the resulting solid product is washed with water, and then dried to obtain lithified zeolite.
[0064] In practice, during the above-mentioned lithiation process, the zeolite molecular sieve can be dispersed in a solution containing the first lithium source and soaked. Specifically, the soaking can be carried out under stirring (i.e., stirring is carried out during the soaking process). After soaking, solid-liquid separation can be carried out by means of filtration, vacuum filtration, etc., and the obtained solid product (powder) can be collected.
[0065] In this embodiment of the invention, the water used may specifically include deionized water.
[0066] In some embodiments, the preparation process of lithiated zeolite includes: subjecting zeolite molecular sieves to multiple lithiation treatments to obtain lithiated zeolite; wherein, for each adjacent two lithiation treatments, the lithium ion concentration of the solution containing the first lithium source used in the previous lithiation treatment is lower than the lithium ion concentration of the solution containing the first lithium source used in the subsequent lithiation treatment, that is, firstly, a solution containing the first lithium source with a lower lithium ion concentration is used for the previous lithiation treatment, and then a solution containing the first lithium source with a higher lithium ion concentration is used for the subsequent lithiation treatment. Through multiple lithiation treatments, it is beneficial to improve the degree of lithiation of the zeolite molecular sieve and increase the lithium content of the obtained lithiated zeolite.
[0067] In some embodiments, the first lithium source may include lithium halide and / or lithium hydroxide (LiOH), wherein lithium halide includes, for example, lithium chloride (LiCl).
[0068] Specifically, the solution containing the first lithium source can be an aqueous solution of the first lithium source formed by dissolving the first lithium source in water.
[0069] In some embodiments, the lithium ion concentration of the solution containing the first lithium source can be greater than or equal to 0.5 mol / L. When multiple lithiation processes are performed, the lithium ion concentration of the solution containing the first lithium source used in each lithiation process is greater than or equal to 0.5 mol / L.
[0070] For example, the lithium ion concentration of the solution containing the first lithium source can be in the range of 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L, or any combination thereof.
[0071] When multiple lithiation processes are performed, the difference in lithium ion concentration of the solution containing the first lithium source used in any two adjacent lithiation processes can be greater than or equal to 0.5 mol / L, for example, it can be a range of 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L or any combination thereof.
[0072] In some embodiments, the preparation process of zeolite molecular sieve may include: mixing an inorganic alkali, a first aluminum source, and water to obtain a first solution; mixing the first solution, alkali solution, and a first silicon source at a temperature ≤10°C, stirring at a temperature less than or equal to 10°C (e.g., -10°C) for at least 10 minutes, and then stirring at room temperature for at least 12 hours; subsequently carrying out a first hydrothermal reaction at 90–110°C, separating the solid and liquid, and drying the obtained solid product to obtain the zeolite molecular sieve.
[0073] Specifically, the time for the first hydrothermal reaction can be 2 to 10 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours or any combination thereof.
[0074] Specifically, in the preparation process of the above-mentioned zeolite molecular sieve, the drying temperature can be 150℃~400℃ (that is, the obtained solid product is dried at 150℃~400℃).
[0075] Specifically, inorganic bases may include strong inorganic bases, specifically alkali metal hydroxides, and further may include sodium hydroxide (NaOH) and / or potassium hydroxide (KOH).
[0076] Specifically, the first aluminum source may include aluminum compounds, specifically aluminum hydroxide (Al(OH)3).
[0077] Specifically, the first silicon source may include silicates, specifically sodium silicate (Na2SiO3).
[0078] In addition, the first solution mentioned above can be an aluminate solution, such as a sodium aluminate solution.
[0079] In addition, the above-mentioned alkaline solution can be an alkaline solution formed by dissolving an alkali in water, wherein the alkali may include inorganic alkalis, specifically alkali metal hydroxides, and further may include sodium hydroxide (NaOH) and / or potassium hydroxide (KOH).
[0080] In practice, an inorganic alkali and a first aluminum source can be dissolved in water, specifically boiling water. After cooling to room temperature, a first solution is obtained. Then, the first solution is cooled by means of an ice bath (e.g., placing the first solution in an ice bath). Under conditions of ≤10℃ and with stirring, the alkali solution is added to the first solution, followed by the addition of a solution containing the first silicon source (such as sodium silicate solution) to mix the first solution, alkali solution, and first silicon source. Subsequently, stirring is maintained for at least 10 minutes under cooling conditions such as an ice bath (temperature ≤10℃), and then returned to room temperature and stirred at room temperature for at least 12 hours. The mixture is then transferred to a hydrothermal reactor for the first hydrothermal reaction. After the first hydrothermal reaction is completed, solid-liquid separation is performed by means of filtration or centrifugation, and the obtained solid product (powder) is dried to obtain zeolite molecular sieve.
[0081] In another embodiment, lithiated zeolite is prepared by a one-step method. The preparation process of lithiated zeolite may include: mixing a second silicon source, a second lithium source and water, and stirring at 40°C to 80°C for 0.5h to 2h to obtain a first mixture; mixing a second aluminum source, a third lithium source and water, and stirring at 40°C to 80°C for 0.5h to 2h to obtain a second mixture; mixing the first mixture and the second mixture, and then carrying out a second hydrothermal reaction at 150°C to 200°C to obtain a hydrothermal reaction product; and sintering the hydrothermal reaction product to obtain lithiated zeolite.
[0082] Specifically, the sintering temperature can be 450℃ to 800℃, for example, a range of 450℃, 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃ or any combination thereof.
[0083] In addition, the sintering time can be 1 hour to 3 hours, for example, 2 hours.
[0084] Specifically, the second silicon source may include silicon dioxide (SiO2).
[0085] Specifically, the second lithium source may include lithium hydroxide (LiOH).
[0086] Specifically, the second aluminum source may include aluminum oxide (Al2O3).
[0087] Specifically, the third lithium source may include lithium hydroxide (LiOH).
[0088] In specific implementation, the second silicon source and the second lithium source can be mixed, water added, heated to a preset temperature, and stirred for a preset time to obtain a first mixed solution (specifically, a suspension); the second aluminum source and the third lithium source can be mixed, water added, heated to a preset temperature, and stirred for a preset time to obtain a second mixed solution (specifically, a suspension); after the first and second mixed solutions have cooled, they are mixed and transferred to a hydrothermal reactor, and stirring is started to carry out a second hydrothermal reaction; after the second hydrothermal reaction is completed, after cooling to room temperature, the obtained hydrothermal reaction product (powder) is collected, washed with water until the washing solution is close to neutral (pH>6.5), and then dried. The drying temperature can be 80℃~120℃ (e.g., 100℃), and the drying time can be 1h~3h (e.g., 2h); then it is transferred to a sintering device such as a muffle furnace for sintering to obtain lithiated zeolite.
[0089] This invention also provides a solid electrolyte membrane, comprising the above-described solid electrolyte composite and / or a solid electrolyte composite prepared according to the above-described method for preparing the solid electrolyte composite. This solid electrolyte membrane has advantages corresponding to the above-described solid electrolyte composite, which will not be elaborated further.
[0090] Specifically, the mass percentage of the solid electrolyte complex in the aforementioned solid electrolyte membrane can be 90% to 100%, for example, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, or any combination thereof.
[0091] Specifically, the aforementioned solid electrolyte membrane may further include a third binder. The mass percentage of the third binder in the solid electrolyte membrane (i.e., the proportion of the mass of the third binder to the total mass of the solid electrolyte membrane) can be 0 to 10%, for example, 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any combination thereof.
[0092] In this embodiment of the invention, the third adhesive can be a conventional adhesive material in the art, such as one or more of PVDF, SBR, hydrogenated nitrile butadiene rubber (HNBR), and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP).
[0093] This invention also provides a battery comprising the aforementioned solid electrolyte membrane. This battery offers advantages corresponding to the aforementioned solid electrolyte composite, which will not be elaborated further.
[0094] In this embodiment of the invention, the battery can be a solid-state battery.
[0095] Generally, the above-mentioned battery also includes a positive electrode and a negative electrode, with a solid electrolyte membrane located between the positive and negative electrode to separate them.
[0096] In the embodiments of the present invention, conventional positive and negative electrode sheets in the art can be used, and there are no particular limitations on this.
[0097] For example, the positive electrode sheet may include a positive current collector and a positive electrode coating present on at least one side surface of the positive current collector. Specifically, the positive electrode coating may be provided on one side surface of the positive current collector, or the positive electrode coating may be provided on both the positive and negative surfaces of the positive current collector.
[0098] The positive current collector can be a conventional positive current collector in the art, for example, the positive current collector may include aluminum foil, but is not limited thereto.
[0099] The positive electrode coating (positive electrode active material layer) may include a positive electrode active material, which may be a conventional positive electrode active material in the art. For example, the positive electrode active material may include a lithium-containing active material capable of lithium ion insertion and extraction, specifically including a ternary positive electrode material, which may include a nickel-cobalt-manganese ternary material (NCM), and the nickel-cobalt-manganese ternary material may include single crystal NCM811.
[0100] In addition, the positive electrode coating may also include a solid electrolyte, which may include a sulfide solid electrolyte and / or a halide solid electrolyte. For the types of sulfide solid electrolytes, please refer to the aforementioned introduction regarding sulfide solid electrolytes in solid electrolyte composites; for the types of halide solid electrolytes, please refer to the aforementioned introduction regarding halide solid electrolytes in solid electrolyte composites, and they will not be repeated here. The solid electrolyte in the positive electrode coating may be the same as or different from the solid electrolyte in the solid electrolyte composite.
[0101] For example, the sulfide solid electrolyte in the positive electrode coating may include Li6PS5Cl, Li 10 GeP2S 12 Li 5.5 PS5Cl 1.5 One or more of the following, halide solid electrolytes may include chloride solid electrolytes, and chloride solid electrolytes may include Li 1.75 ZrCl 4.75 O 0.5 .
[0102] In addition, the positive electrode coating may also include conductive agents and / or binders, which can be conventional materials in the art. For example, the conductive agent may include one or more of carbon black, carbon nanotubes (CNT), acetylene black, graphene, Ketjen black, and carbon fiber, and the binder may include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, etc.
[0103] For example, the negative electrode sheet may include a negative current collector and a negative electrode material layer present on at least one side surface of the negative current collector. Specifically, the negative electrode material layer may be provided on one side surface of the negative current collector, or negative electrode material layers may be provided on both the negative and negative sides of the negative current collector.
[0104] The negative electrode current collector can be a conventional negative electrode current collector in the art. For example, the negative electrode current collector may include copper foil and / or carbon-coated copper foil, but is not limited to this.
[0105] The negative electrode material layer may include conventional negative electrode materials in the art, such as lithium copper sheet, or the negative electrode material layer may include a negative electrode coating, which may include a negative electrode active material. The negative electrode active material may be a conventional negative electrode active material in the art, such as graphite, silicon-based materials, or lithium metal materials.
[0106] In addition, the negative electrode coating (negative electrode active material layer) may also include a solid electrolyte, which may include a sulfide solid electrolyte and / or a halide solid electrolyte. For the types of sulfide solid electrolytes, please refer to the aforementioned introduction regarding sulfide solid electrolytes in solid electrolyte composites; for the types of halide solid electrolytes, please refer to the aforementioned introduction regarding halide solid electrolytes in solid electrolyte composites, and they will not be repeated here. The solid electrolyte in the negative electrode coating may be the same as or different from the solid electrolyte in the solid electrolyte composite.
[0107] For example, the sulfide solid electrolyte in the negative electrode coating may include Li6PS5Cl, Li 10 GeP2S 12 Li 5.5 PS5Cl 1.5 One or more of the following, halide solid electrolytes may include chloride solid electrolytes, and chloride solid electrolytes may include Li 1.75 ZrCl 4.75 O 0.5 .
[0108] In this embodiment of the invention, the solid electrolyte in any two of the positive electrode, negative electrode, and solid electrolyte membrane can be the same or different.
[0109] In addition, the negative electrode coating may also include conductive agents and / or binders, which can be conventional materials in the art. For example, conductive agents may include one or more of carbon black, carbon nanotubes (CNT), acetylene black, graphene, Ketjen black, and carbon fiber, and binders may include one or more of carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.
[0110] In this embodiment of the invention, the battery can be manufactured by conventional methods in the art, and there are no particular limitations thereto.
[0111] This invention also provides a battery pack including the above-described battery, which has advantages corresponding to the above-described solid electrolyte composite, and will not be described in detail here.
[0112] Generally, a battery pack includes multiple batteries as individual cells, which are connected to form the battery pack. These batteries can be electrically connected using methods conventional in the art, such as series connection, parallel connection, or a combination of these connection methods, without any particular limitation.
[0113] This invention also provides an electrical device, including the battery or battery pack described above. This electrical device has advantages corresponding to the solid electrolyte complex described above, which will not be elaborated further.
[0114] The electrical equipment in the embodiments of the present invention can be conventional electrical equipment in the art, such as power equipment (e.g., electric vehicles, electric cars), electronic equipment (e.g., mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (e.g., watches, bracelets, VR glasses, etc.), energy storage power stations, etc., and there are no particular limitations.
[0115] The present invention will be further described below through specific embodiments.
[0116] Example 1
[0117] (1) Preparation of zeolite molecular sieves
[0118] Dissolve 2g NaOH and 0.98g Al(OH)3 in 50mL of boiling water, cool to room temperature, and prepare the first solution;
[0119] Dissolve 2.9g NaOH in 32.6g deionized water, cool to room temperature, and prepare an alkaline solution;
[0120] Add 22.35g of Na2SiO3 to an appropriate amount of deionized water to prepare a sodium silicate solution with a mass concentration of 32wt%.
[0121] In an ice bath at -10°C, the alkaline solution was slowly added to the first solution while stirring, followed by the slow addition of sodium silicate solution. The mixture was then stirred for 1 hour in the ice bath environment, followed by stirring at room temperature for 24 hours. The mixture was then transferred to a hydrothermal reactor and reacted at 98°C for 8 hours. The mixture was then filtered to obtain zeolite powder (zeolite molecular sieve).
[0122] (2) Preparation of lithiated zeolite: 5g of zeolite powder was added to 20mL of 5mol / L LiCl solution and stirred for 2h. Then the mixture was filtered and the powder was collected. The obtained solid product (powder) was washed once with deionized water and then dried to obtain lithiated zeolite.
[0123] (3) Preparation of solid electrolyte complex
[0124] 1g of lithium zeolite was mixed with 9g of Li6PS5Cl and ball-milled for 6h under an inert atmosphere to obtain a solid electrolyte complex.
[0125] Example 2
[0126] 1. Preparation of lithium zeolite
[0127] LiOH and SiO2 were mixed in a beaker, water was added, and the mixture was heated to 60°C and stirred for 1 hour to prepare the first mixture (suspension).
[0128] LiOH and Al2O3 were mixed in a beaker, water was added, and the mixture was heated to 60°C and stirred for 1 hour to prepare a second mixture (suspension); wherein the molar ratio of LiOH, SiO2, Al2O3 and water used was LiOH:SiO2:Al2O3:H2O=20:0.5:2.5:600;
[0129] After the first and second mixtures cooled, they were mixed and transferred to a hydrothermal reactor. Stirring was started, and the mixture was reacted at 170°C for 72 hours. After cooling, the resulting hydrothermal reaction product (powder) was collected, washed with deionized water until the pH of the washing solution was close to neutral (8 > pH > 6.5), then dried at 100°C for 2 hours, and finally transferred to a muffle furnace for sintering at 600°C for 2 hours to obtain lithiated zeolite (its molecular formula is Li2(Al2Si4O3)2). 12 )).
[0130] 2. Preparation of solid electrolyte complexes
[0131] 1g of lithium zeolite was mixed with 9g of Li6PS5Cl and ball-milled for 6h under an inert atmosphere to obtain a solid electrolyte complex.
[0132] Examples 2 through 9 differ from Example 1 in that the mass ratio of lithiated zeolite to solid electrolyte in the solid electrolyte composite (mass ratio of zeolite to solid electrolyte in Table 1), the type of solid electrolyte, and the lithium content (mass percentage) in the lithiated zeolite molecular sieve are all different, as detailed in Table 1. Except for the differences shown in Table 1, all other conditions are the same. The particle size of the lithiated zeolite molecular sieve in each example is between 0.5 μm and 10 μm.
[0133] The difference between the preparation process of the solid electrolyte complex in Example 8 and Example 1 is that in step (2), a LiOH solution with a concentration of 1 mol / L is used instead of a LiCl solution with a concentration of 5 mol / L, while the other steps and conditions are the same as in Example 1.
[0134] The difference between the preparation process of the solid electrolyte complex in Example 9 and Example 1 is that in step (2), four lithiation treatments (lithium-ion exchange) are performed. The first lithiation treatment uses 20 mL of 0.5 mol / L LiCl solution, the second lithiation treatment uses 20 mL of 1 mol / L LiCl solution, the third lithiation treatment uses 20 mL of 3 mol / L LiCl solution, and the fourth lithiation treatment uses 20 mL of 5 mol / L LiCl solution. After each lithiation treatment, the solid product is filtered and collected, and then the next lithiation treatment is performed until the last lithiation treatment is completed. After that, the solid product (powder) is filtered and collected, washed once with deionized water, and then dried to obtain lithiated zeolite.
[0135] Comparative Example 1: The difference from Example 1 is that in step (3), lithium zeolite was not added to the solid electrolyte (Li6PS5Cl) (i.e., steps (1) to (3) were not performed in Comparative Example 1. The preparation process of the solid electrolyte in Comparative Example 1 is as follows: 10g of Li6PS5Cl was ball-milled in an inert atmosphere for 6h to obtain the solid electrolyte). The remaining steps and conditions are the same as in Example 1.
[0136] Comparative Example 2: The difference from Example 1 is that the zeolite molecular sieve was not subjected to the lithiation treatment in step (2) (i.e., in step (3) of Comparative Example 2, the zeolite molecular sieve obtained in step (1) was used to replace the lithified zeolite in step (3) of Example 1), and the remaining steps and conditions were the same as in Example 1.
[0137] Comparative Example 3: The difference from Example 1 is that in step (3), commercial 4A zeolite molecular sieve is used to replace the lithium zeolite in Example 1 (that is, Comparative Example 3 does not perform steps (1) and (2), and in step (3) of Comparative Example 3, 9g of Li6PS5Cl is mixed with 1g of commercial 4A zeolite molecular sieve and ball-milled in an inert atmosphere for 6h to obtain a solid electrolyte complex). The remaining steps and conditions are the same as in Example 1.
[0138] Comparative Examples 4 to 5: The difference from Example 1 is that the mass ratio of lithium zeolite to solid electrolyte in the solid electrolyte complex is different, as shown in Table 1. Except for the differences shown in Table 1, the other conditions are the same.
[0139] The performance of the solid electrolyte materials of each embodiment and comparative example (i.e., the solid electrolyte composites prepared in Examples 1 to 11, Comparative Examples 2 to 5, and the solid electrolyte prepared in Comparative Example 1) was tested by the following process, and the results are shown in Table 1.
[0140] 1. Ionic conductivity testing method
[0141] (1) Battery assembly and ionic conductivity testing methods
[0142] S101. Battery Assembly: Assemble in an inert gas glove box. Place a piece of carbon-coated aluminum foil at the bottom of the mold battery (Φ=10mm). Weigh 0.125g of solid electrolyte material powder and pour it into the mold battery. Gently vibrate to make it basically flat. Install the upper pressure head to press the pre-pressed powder at a pressure of 2t. Depressurize, remove the upper pressure head, install another piece of carbon-coated aluminum foil, and flatten it. Install the upper pressure head and press at a pressure of 10t. Tighten the mold battery sealing ring. Depressurize. Remove the mold battery from the glove box and place it in the mold battery fixture. The fixture is insulated from the mold battery by aluminum-plastic film on both the top and bottom. Tighten the screws to fix it. Use a hydraulic press to press at a pressure ≥4t. Tighten the screws under pressure and then depressurize.
[0143] S102. Solid electrolyte sheet thickness measurement: Apply a small amount of Vaseline to the upper and lower mold heads of the mold battery (Φ=10mm), weigh out the same amount of solid electrolyte powder as in the previous step, press under 10t pressure, demold to obtain solid electrolyte sheet, and use a micrometer to measure the thickness L of the solid electrolyte sheet.
[0144] S103. Ionic Conductivity Test: Electrochemical impedance spectroscopy (EIS) was performed on the model battery using an electrochemical workstation (Biologic VMP-300). Test frequency: 1MHz (high frequency), 100Hz (low frequency); amplitude: 5mV; test bias: 0V vs. Eoc (open circuit voltage). After the test, the real part value corresponding to the semicircular endpoint in the high-frequency region of the EIS curve was read. The real part R was used as the resistance value for calculating ionic conductivity.
[0145] Ionic conductivity can be calculated using the following formula:
[0146]
[0147] Where: L—thickness of the solid electrolyte sheet (cm);
[0148] R—The resistance value (Ω) of the solid electrolyte, which is measured by the above method;
[0149] A—End face area of the solid electrolyte sheet (Φ=10mm)(cm²) 2 That is, 3.14 * (1 / 2) 2 ;
[0150] (2) Following steps S101 to S103 above, test the ionic conductivity of the solid electrolyte material powder that has not been exposed to the environment at -45℃. The measured ionic conductivity before exposure is shown in Table 2.
[0151] (3) Take 1g of solid electrolyte material powder, spread it on a petri dish with a diameter of 75mm, and expose it in an environment with a dew point of -45℃ for 12h; then follow the above steps S101~S103 to test the ionic conductivity of the exposed solid electrolyte material powder. The measured ionic conductivity after exposure is shown in Table 2.
[0152] 3. Hydrogen sulfide production test method
[0153] In a constant temperature and humidity chamber at 25℃ and 50%, a 35L sealable container was placed. 0.1g of solid electrolyte material sealed in an inert atmosphere was quickly spread in the 35L container and then the container was sealed. The hydrogen sulfide concentration in the 35L container was continuously monitored using a hydrogen sulfide sensor, and the highest value of hydrogen sulfide concentration within 2 hours was taken as the hydrogen sulfide production.
[0154] 4. Solid-state battery capacity retention test
[0155] (1) Exposure treatment: Take 1g of solid electrolyte material powder, spread it on a petri dish with a diameter of 75mm, and expose it in an environment with a dew point of -45℃ for 12h to obtain the exposed solid electrolyte material powder.
[0156] (2) Solid-state battery fabrication using exposed solid electrolyte material powder: NCM811 (LiNi) was assembled in an inert atmosphere glove box. 0.8 Co 0.1 Mn 0.1O2) was used to test the Li / In alloy battery. A copper foil was placed at the bottom of a mold battery (Φ=10mm). Approximately 5mg of Li was weighed and placed on the copper foil, and approximately 100mg of In was weighed and placed on the lithium copper. The battery was then pressed under a pressure of 2t. 0.1g of solid electrolyte material powder was weighed and poured into the mold battery, and the battery was pressed again under a pressure of 2t. 8mg of single-crystal NCM811 powder and 2mg of D were weighed... 50 =1μm Li 5.5 PS5Cl 1.5 Grind and mix the powder evenly, pour it into the mold battery, press it under 2t pressure, and tighten the mold battery sealing ring. Release the pressure, remove the mold battery from the glove box, and place it in the mold battery clamp. Insulate the mold battery from both the top and bottom of the clamp with aluminum-plastic film, and tighten the screws to secure it. Press it using a hydraulic press with a pressure ≥4t. Tighten the screws while maintaining pressure, then release the pressure.
[0157] (3) Solid-state battery capacity retention test
[0158] Using a charge-discharge test cabinet, the solid-state battery was charged and discharged at 0.1C (charge and discharge current of 0.16mA) for 2 cycles. The 0.1C discharge capacity of the solid-state battery is shown in Table 2.
[0159] Using a charge-discharge test cabinet, the solid-state battery was charged and discharged at 0.3C (charge and discharge current of 0.48mA) for 2 cycles. The 0.3C discharge capacity of the solid-state battery was measured and is shown in Table 2.
[0160] Using a charge-discharge test cabinet, the solid-state battery was charged and discharged at 0.3C (charge and discharge current of 0.48mA) for 20 cycles. The capacity retention rate of the solid-state battery after 20 cycles at 0.3C was measured (capacity retention rate = the ratio of the discharge capacity after 20 cycles at 0.3C to the discharge capacity of the first cycle at 0.3C). The results are shown in Table 2.
[0161] Table 1
[0162]
[0163] Table 2
[0164]
[0165] As can be seen from Table 1, compared with Comparative Examples 1 to 5, in Examples 1 to 15, by using lithium zeolite to combine with solid electrolyte to form a solid electrolyte complex, the stability of the solid electrolyte complex can be improved. The solid electrolyte complex has both high ionic conductivity and electronic conductivity. It has high ionic conductivity and other properties after exposure, which can suppress the decrease of ionic conductivity and other properties of the solid electrolyte complex. It has a high ionic conductivity retention rate. At the same time, the battery has high capacity and capacity retention rate, showing good cycle life and cycle stability.
[0166] Further, as can be seen from Examples 1, 3, 4, 10 and 12, Examples 1, 3, 4 and 10, by further controlling the mass ratio of lithium zeolite to solid electrolyte in the solid electrolyte complex within the range of 1:(4 to 50), are beneficial to further improve the ionic conductivity and stability of the solid electrolyte complex, thereby enhancing the rate performance and cycle capacity retention of the battery.
[0167] Further, as can be seen from Examples 2, 8, 9, and 13 to 15, in Examples 2, 8, 9, and 14, by further controlling the lithium content in the lithiated zeolite within the range of 1.8% to 6.5%, it is beneficial to further improve the ionic conductivity and stability of the solid electrolyte complex, thereby enhancing the rate performance and cycle capacity retention of the battery.
[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A solid electrolyte complex, characterized in that, It includes lithium zeolite and solid electrolyte, wherein the mass ratio of lithium zeolite to solid electrolyte is 1:(4-70).
2. The solid electrolyte composite according to claim 1, characterized in that, The mass ratio of the lithium zeolite to the solid electrolyte is 1:(4-50).
3. The solid electrolyte complex according to claim 1, characterized in that, The lithium content in the lithiated zeolite is 1.5% to 25% by mass.
4. The solid electrolyte complex according to claim 1, characterized in that, The lithium content in the lithiated zeolite is 1.8% to 6.5% by mass.
5. The solid electrolyte complex according to any one of claims 1-4, characterized in that, The solid electrolyte includes sulfide solid electrolytes and / or halide solid electrolytes.
6. The solid electrolyte composite according to claim 5, characterized in that, The sulfide solid electrolyte includes Li 6-a PS 5-a X 1+a One or more of LGPS, LPS, and Li2S-P2S5 glass-ceramic solid electrolytes, wherein the Li 6-a PS 5-a X 1+a In this context, X represents a halogen, and 0 ≤ a ≤ 0.8; And / or, the halide solid electrolyte includes Li b MX c O d The Li b MX c O d In this context, X represents a halogen, M represents a transition metal element, 1≤b≤3, 1≤c≤6, and 0≤d≤1.
7. A method for preparing a solid electrolyte complex according to any one of claims 1-6, characterized in that, Includes the following steps: The mixture containing the lithium zeolite and the solid electrolyte is ball-milled to obtain the solid electrolyte composite.
8. The method for preparing the solid electrolyte complex according to claim 7, characterized in that, The preparation process of the lithiated zeolite includes: performing at least one lithiation treatment on the zeolite molecular sieve to obtain the lithiated zeolite; the lithiation treatment process includes: soaking the zeolite molecular sieve in a solution containing a first lithium source for at least 0.5 h.
9. The method for preparing the solid electrolyte complex according to claim 8, characterized in that, The first lithium source includes lithium halide and / or lithium hydroxide; And / or, the lithium ion concentration of the solution containing the first lithium source is greater than or equal to 0.5 mol / L; And / or, the preparation process of the lithiated zeolite includes: subjecting the zeolite molecular sieve to multiple lithiation treatments to obtain lithiated zeolite; wherein, for each adjacent two lithiation treatments, the lithium ion concentration of the solution containing the first lithium source used in the previous lithiation treatment is less than the lithium ion concentration of the solution containing the first lithium source used in the subsequent lithiation treatment.
10. The method for preparing the solid electrolyte complex according to claim 8 or 9, characterized in that, The preparation process of the zeolite molecular sieve includes: mixing an inorganic alkali, a first aluminum source, and water to obtain a first solution; mixing the first solution, alkali solution, and a first silicon source at a temperature ≤10℃, stirring for at least 10 min at a temperature less than or equal to 10℃, and then stirring at room temperature for at least 1 h; subsequently carrying out a first hydrothermal reaction at 90–110℃, separating the solid and liquid, and drying the obtained solid product to obtain the zeolite molecular sieve.
11. The method for preparing the solid electrolyte complex according to claim 10, characterized in that, The inorganic base includes sodium hydroxide and / or potassium hydroxide; And / or, the first aluminum source includes aluminum hydroxide; And / or, the first silicon source comprises silicates; And / or, the alkali in the alkaline solution includes sodium hydroxide and / or potassium hydroxide; And / or, the duration of the first hydrothermal reaction is 2 to 10 hours.
12. The method for preparing the solid electrolyte complex according to any one of claims 7-9, characterized in that, The preparation process of the lithium zeolite includes: The second silicon source, the second lithium source, and water are mixed and stirred at 40℃~80℃ for 0.5h~2h to obtain the first mixture. The second aluminum source, the third lithium source and water are mixed and stirred at 40℃~80℃ for 0.5h~2h to obtain the second mixture; The first mixture and the second mixture are mixed, and then a second hydrothermal reaction is carried out at 150℃~200℃ to obtain the hydrothermal reaction product. The hydrothermal reaction products are sintered to obtain the lithium zeolite.
13. The method for preparing the solid electrolyte complex according to claim 12, characterized in that, The second silicon source includes silicon dioxide; And / or, the second lithium source includes lithium hydroxide; And / or, the second aluminum source includes aluminum oxide; And / or, the third lithium source includes lithium hydroxide; And / or, the sintering temperature is 450℃~800℃.
14. A solid electrolyte membrane, characterized in that, Includes the solid electrolyte complex according to any one of claims 1-6 and / or the solid electrolyte complex prepared according to the preparation method of the solid electrolyte complex according to any one of claims 7-13.
15. The solid electrolyte membrane according to claim 14, characterized in that, The solid electrolyte complex in the solid electrolyte membrane has a mass percentage content of 90% to 100%.
16. The solid electrolyte membrane according to claim 14 or 15, characterized in that, It also includes a third binder, wherein the mass percentage of the third binder in the solid electrolyte membrane is 0-10%.
17. A battery, characterized in that, Includes the solid electrolyte membrane according to any one of claims 14-16.
18. The battery according to claim 17, characterized in that, The battery is a solid-state battery.
19. A battery pack, characterized in that, Includes the battery as described in claim 17 or 18.
20. An electrical appliance, characterized in that, Includes the battery as described in claim 17 or 18 or the battery pack as described in claim 19.